Free-living use of artificial pancreas for children with type 1 diabetes: systematic review - Klemen Dovc (Endocrinology Research Centre, 2018)
BACKGRAUND: A closed-loop glucose control system or ‘artificial pancreas’ consists of three components – a Continuous Glucose Monitor (CGM), infusion pumps to deliver hormone(s) and a sophisticated dosing algorithm to control hormone delivery. In the past years, numerous studies with closed-loop system devices were conducted with gradual shift to out-of-hospital environment and with lengthening study duration. AIMS: To compare efficacy and safety of closed-loop insulin pump use in children with type 1 diabetes mellitus in compare with conventional insulin treatment (continuous subcutaneous insulin infusion (CSII) with our without CGM) based on randomized control trials data (RCT). METHODS: In the systematic review we have include 28 randomized controlled trials results indexed in PubMed, Medline databases published till 15 June 2017. The efficacy on metabolic control in this study evaluated by the proportion of time within target range (preferably 70 to 180 mg/dl if reported) and mean (median) glucose based on sensor measurements, and the safety evaluated by time in hypoglycemia (below 70 mg/dl if reported). RESULTS: Increased time in range in the night period was observed in all RCT. Only 3 RCT showed decrease of the time in range within 24 h evaluation period. In one RCT the significant positive differences have been shown in the time in range for dual hormone closed-loop glucose control system in compare with insulin-only artificial pancreas. Mean glycaemia and glucose variability changes were not in the same manner in different RCT, both in the night only and in 24 h estimation period. Night hypoglycemia duration decreased in most RCT with closed-loop control in compare with CSII, and increased only in 2 RCT. When all-day estimation period the time in hypoglycemia changed not in the same manner in different RCT. Valuable methodology differences of the glycaemic control estimation within observed RCT brought significant complications in the data analysis and made impossible the results quantitative estimation to prepare a metaanalysis. CONCLUSIONS: Much work has been done to develop effective and safe artificial pancreas, but not all RCTs confirmed advantages of closed-loop glucose control in compare with CSII in children and adolescents in real life. More research with prospective randomized control design required to prove benefits of closed-loop glucose control. Further RCTs should have an uniform methodology for glycemic control assessment and long duration that will allow to use cumulative measures in a closed-loop efficacy estimation (HbA1c).